ACTR-68. INITIAL TREATMENT OF GBM WITH A KETOGENIC DIET ALONG WITH RADIATION AND CHEMOTHERAPY: FEASIBILITY, TOXICITY AND RESPONSE. (5th November 2018) - Schwartz, Kenneth; Noel, Mary; Nikolai, Michele; Olson, Karl; Elnabtity, Mohamed; Zakem, Micheal; Clark, Justin; Figueroa, Bryan; Chang, Howard
Abstract: INTRODUCTION: We initiated and now report early outcomes of a pilot clinical trial study using a ketogenic diet (KD) combined with radiation and chemotherapy as initial therapy for aggressive gliomas (glioblastoma, GBM). METHODS: Eligibility criteria included: 1. Tissue diagnosis; 2. Age over 18; 3. ECOG performance status of 2 or better; and 4. Not having diabetes or being pregnant. An isocaloric KD diet with 3:1 weight ratio of fat to combined weight of carbohydrate and protein was supervised by an experienced dietitian. Per protocol the KD together with radiation and chemotherapy was maintained for 6 weeks. RESULTS: 9 patients (mean age 45, 8F, 1M) completed 6 weeks of this trial. Blood counts, chemistries, lipid profiles and uric acids were not markedly changed. No other significant side effects were observed. Ketosis was maintained for the 6 week study period with blood ketone and glucose levels checked twice daily: The ketones ranged between 0.9 and 4.1 and glucose ranged between 80.3 and 120. Patients' daily AM weights decreased on average < 10% during the study. 3 patients (mean age 28) showed no progression of their gliomas at 34 (IDH +), 19 (IDH +), and 25 (IDH WT) months since diagnosis. 6 patients (mean age 54) have died at 25, 25, 13, 12, 9 and 9 months after diagnosis. CONCLUSIONS: 1. Combining an adjuvant KD with standard therapy of radiation and chemotherapy right after tissue diagnosis is feasible and safe. 2. Daily measurements of blood ketones and glucose are necessary to assure continued ketosis; 3. KD may be a helpful adjuvant initial treatment of GBM patients, especially in younger patients. A larger study will be required to test this hypothesis.